Evaluation of thymic dimensions in patients with multisystem inflammatory syndrome - Doğan, Adil; Güngör, Şükrü; Güllü, Ufuk Utku; İpek, Sevcan and Yurttutan, Nursel and Yurttutan, Sadık (The Turkish Journal of Pediatrics, 2022)
Background. Multisystem inflammatory syndrome (MIS-C) is the most important complication of COVID-19 in the pediatric population. Unfortunately, this problem is an unpredictable situation in patients with COVID-19. We aimed to evaluate the effects of MIS-C on thymus dimensions in pediatric patients. Methods. We retrospectively analyzed the files of 368 pediatric patients aged 2-18 years, who were diagnosed with COVID-19. Computer Tomography (CT) images of 22 patients diagnosed with COVID-19 and 10 patients diagnosed with MIS-C were evaluated in detail by two board-certified radiologists. Eighteen age and sexmatched patients who applied to the emergency department of our hospital for any reason and had a CT scan for any reason were selected as the control group. The data of both groups were statistically compared. Results. Considering the differences between the groups in terms of laboratory data, monocytes, hemoglobin, and platelet were significantly lower in the MIS-C group than the other groups. Procalcitonin, C- reactive protein, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and proBNP levels were statistically significantly higher in the MIS-C group compared to the other groups Regarding the differences in thymus dimensions, thymus AP diameter, transverse diameter, length, thickness, and volume were significantly higher in the MIS-C group than in the other groups There was a significant positive correlation between the transverse diameter of the thymus and CRP, procalcitonin, pro-brain natriuretic peptide (proBNP), and NLR levels. Conclusions. Our study shows that thymus dimensions and acute phase reactants are higher in pediatric patients in the MIS-C group. Also, thymus transverse diameter, thymus thickness, and PLR values pose a risk for the development of MIS-C. More research is needed on the role of the thymus gland in the pathogenesis and diagnosis of MIS-C.